2020
DOI: 10.1108/lhtn-11-2019-0085
|View full text |Cite
|
Sign up to set email alerts
|

Marketing intangibles: the case of library services in higher education institutions

Abstract: Purpose This paper aims to investigate the adoption of marketing techniques in academic libraries in Ghana, and how they are applied in the promotion of their services to patrons. Design/methodology/approach Adopting the qualitative research approach, a total of 21 professional and para-professional library staff from three private universities participated in the study. The main data collection instrument was the use of semi-structured interviews. Data gathered was analysed, discussed and presented thematic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 37 publications
1
2
0
Order By: Relevance
“…The finding of the present study is consistent with that of Edewor et al (2016, p. 298), carried out in the African context, who found that libraries rarely adopted social-networking technologies and did not use online marketing strategies to create awareness to their users. In addition, the finding supports the finding of Ofori et al (2020, p. 16) that library orientation is the most common library marketing approach to students in Ghana. Furthermore, in the present study, the quantitative data showed that 52.1% of the distance learners indicated to a very large extent that library marketing facilitated the use of library services and resources.…”
Section: Discussion Conclusion and Recommendationssupporting
confidence: 86%
See 1 more Smart Citation
“…The finding of the present study is consistent with that of Edewor et al (2016, p. 298), carried out in the African context, who found that libraries rarely adopted social-networking technologies and did not use online marketing strategies to create awareness to their users. In addition, the finding supports the finding of Ofori et al (2020, p. 16) that library orientation is the most common library marketing approach to students in Ghana. Furthermore, in the present study, the quantitative data showed that 52.1% of the distance learners indicated to a very large extent that library marketing facilitated the use of library services and resources.…”
Section: Discussion Conclusion and Recommendationssupporting
confidence: 86%
“…The study identified the most frequently adopted marketing strategies in academic libraries in those libraries as flyers, handbills, leaflets, bulletins, newsletters and orientation programmes. In Ghana, research suggests that students define library orientation as the most frequently used tool for library marketing (Ofori et al , 2020, p. 16). Though these strategies are well known in the library arena, the selection and level of application of these tools are used differently for various purposes by individual institutions.…”
Section: Introductionmentioning
confidence: 99%
“…The twenty-first-century information provision function is no longer a monopoly of libraries. Notwithstanding their huge collections, twenty-first-century libraries across the global divide, (including academic libraries), are competing with other information service providers, such as big publishing houses, online book dealers, academic database vendors and the internet in enhancing easy access to information (Ofori et al , 2020). Despite the huge investments and collection development efforts made by academic libraries, research has established that these library collections are often underused, resulting in a waste of time, space and money (Manda, 2005; Kinengyere, 2007; Ndinoshiho, 2010; Baro et al , 2011; Habanabakize, 2018).…”
Section: Research Problemmentioning
confidence: 99%